Committee on Corporate Sector Participation in Higher Education Report of NR Narayana Murthy Committee 2012 - Planning Commission (Planning Commission Government of India, 2012)
The NR Narayana Murthy Committee Report (2012) examines the role of corporate participation in enhancing India’s higher education system, which faces challenges including low Gross Enrollment Ratio, inadequate infrastructure, faculty shortages, poor research output, and limited employability of graduates. The committee recommends creating enabling conditions through institutional autonomy, fiscal incentives, and access to infrastructure; improving quality and research via corporate-funded R&D programs and faculty development; and promoting infrastructure development by establishing Centers of Excellence, new universities, and technology parks. The report proposes the creation of 20 national knowledge clusters and upgrading 75 institutions to world-class standards, requiring an estimated investment of Rs. 40,000 crores during the 12th Five Year Plan. A nodal agency is suggested to facilitate corporate-academic collaboration, ensuring effective resource utilization. The report emphasizes that strategic corporate engagement can transform higher education into a driver of innovation, skill development, and economic growth, aligning India with global educational standards.
Planning Commission Government of India New Delhi
Keywords: Corporate Participation; Higher Education; Institutional Autonomy; Research Funding; Infrastructure Development; Knowledge Clusters; Centers of Excellence; Employability; Public-Private Partnership; Quality Improvement; Nodal Agency; Global Standards